2020
DOI: 10.3389/fspor.2020.551542
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Linear and Non-linear Measurements of Post-stroke Walking Activity and Their Relationship to Weather

Abstract: Background: Stroke survivors are more sedentary than the general public. Previous research on stroke activity focuses on linear quantities. Non-linear measures, such as Jensen-Shannon Divergence and Lempel-Ziv Complexity, may help explain when and how stroke survivors move so that interventions to increase activity may be designed more effectively. Objectives: Our objective was to understand what factors affect a stroke survivor's physical activity, including weather, by characterizing activity by step counts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Based on the results of the analysis (Table 1), the authors identified physical activity / physical exercise that can be performed by stroke patients including progressive resistance and balance (PRB) training 18,19 , locomotors training: (walking on a treadmill with body weight support and walking on the ground) 18 , selective movements of the upper and lower trunk of the body in a supine position and sitting using a stable support / base or unstable support (Swiss ball) 20 , core stability training 21,22 , aerobic (AT) and resistance training (RT) 23,24 , aerobic training 25 , walking exercises 26 , and task-oriented training 27,28 .…”
Section: Physical Activity Of Stroke Patientsmentioning
confidence: 99%
“…Based on the results of the analysis (Table 1), the authors identified physical activity / physical exercise that can be performed by stroke patients including progressive resistance and balance (PRB) training 18,19 , locomotors training: (walking on a treadmill with body weight support and walking on the ground) 18 , selective movements of the upper and lower trunk of the body in a supine position and sitting using a stable support / base or unstable support (Swiss ball) 20 , core stability training 21,22 , aerobic (AT) and resistance training (RT) 23,24 , aerobic training 25 , walking exercises 26 , and task-oriented training 27,28 .…”
Section: Physical Activity Of Stroke Patientsmentioning
confidence: 99%